Facile Synthesis of High 001 Facets Dominated BiOCl Nanosheets and Their Selective Dye-Sensitized Photocatalytic Activity Induced by Visible Light. (18th January 2016) - Zhang, Da; Chen, Liang; Xiao, Chengjing; Feng, Jing; Liao, Lingmin; Wang, Zaiqin; Wei, Tao
Abstract : Single-crystal BiOCl nanosheets, with high 001 facets exposed, were synthesized through a facile hydrolysis reaction under general atmospheric pressure, without adding any organic surfactant or agent. The thickness of the BiOCl nanosheets is about 20 nm, and the diameter is arranged from 200 to 400 nm. The structure of the BiOCl nanosheets was characterized by X-ray diffraction, energy disperse X-ray spectrum, transmission electron microscopy, and selective area electron diffraction. Moreover, three different dyes were used as model molecules to test the photocatalytic activity of BiOCl nanosheets under visible light. It was found that the BiOCl nanosheets possess selective photocatalytic behavior as their activity over RhB is much higher than that over MO or MB. Based on the analysis of the experimental results, the potential mechanism was discussed.